Effect of physiological pH on the molecular characteristics, rheological behavior, and molecular dynamics of κ-carrageenan/casein - Guo, Juanjuan; Zhu, Siliang; Chen, Peilin; Liu, Zhiyu; Lin, Luan; Zhang, Jie (Frontiers in Nutrition, 2023)
During gastrointestinal digestion, κ-carrageenan (κ-CGN) undergoes physicochemical changes, which associated with the risk of colitis. To understand the effect of physiological pH on the conformational transition and binding stability of κ-CGN and κ-carrageenan/casein (κ-CC), we conducted experiments at pH 3.0 (gastric environment) and pH 7.0 (intestinal environment). We evaluated zeta potential, free sulfate group content, Fourier transform infrared spectroscopy, thermodynamic properties, microstructure, and molecular mechanism. Our results revealed that the helical conformation of κ-CGN and κ-CC were more ordered and stable, and sulfate group exposure both lower in the intestinal environment (pH 7.0). However, in gastric environment (pH 3.0), the charge density of κ-CGN decreased, accompanied by random curling conformation and free sulfate group content increased. In contrast, the intermolecular interactions between κ-CGN and casein increased in gastric acid environments due to casein flocculation and secondary structure folding, and significantly reduced the exposure of free sulfate groups of κ-CGN. Our research results provide an important theoretical basis for elucidating the molecular mechanism and structure-activity relationship of κ-CGN under casein matrix to protect the mucosal barrier and inhibit colitis, and are of great significance for guiding and expanding the safe application of κ-CGN.